Media Localism : The Policies of Place - Ali, Christopher (Book collections on Project MUSE., 2017)
We live in a boosterish era that exhorts us to play local and buy local. But what does it mean to support local media? How should we define local media in the first place? Christopher Ali delves into our ideas about localism and their far-reaching repercussions for the discourse of federal media policy and regulation.